SINTESIS DAN SIFAT MEKANIK BIOKOMPOSIT SERAT HELICONIA-POLIESTER - Akhiruddin Maddu (Jurnal Biofisika, 2012)
In this study, polyester-fiber heliconia biocomposites has been created and tested on its mechanical properties. Biocomposites was manufactured begins by separating the fibers.  it  consists  of  three  stages,  namely  chlorization,  alkaline  leaching  and extraction.  After  that,  the  manufacture  of  composites  made  with  Hand  Lay-up techniques.  Three  samples  with  variations in  fiber content,  ie without  the addition of fiber,  0.54  g  and  2.08  g  fiber.  Characterization  of  samples  includes  tensile  test, hardness,  and  impact.  The test results known that  the  tensile  strength  and  hardness increased  with  increasing  the  amount  of fiber  heliconia.  Impact  test  shows  sample values optimum working temperature is 10°C